Clinical Evaluation of Patients with Vestibular Dysfunction - Vijay Renga (Neurology Research International)
Dizziness is a common reason for outpatient neurology consultation. Oftentimes, a complete workup by general practitioner, including MRI brain fails to reveal a cause. Some patients would have also undergone an ENT evaluation before approaching neurology for an answer. Such scenarios provide a challenge as well as opportunity for the neurologist to exercise their knowledge and clinical skills in arriving at a diagnosis. Conditions like ‘Unspecified Vestibular Dysfunction’ and ‘Presbyvertigo’ are often the underlying causes, which are either not recognized or misdiagnosed as BPPV, psychogenic or perceptive dizziness. This article’s goal is to help understand vestibular system and diagnose vestibular dysfunction in clinical practice.